Physical Well-being & Health Care Resource Utilization Among the Elderly in Banda District: A Cross-Sectional Study - Gupta, Sandeep Kumar; Kaushal, Suneel Kumar; Maroof, Mohd; Singh, Lal Divakar (Indian Journal of Community Health, 2025)
Background: The global elderly population is rapidly increasing, with numbers projected to rise from 740 million to 2.1 billion by 2050. In India, the elderly population is expected to increase by 56 million from 2021-2031. Uttar Pradesh has one of the largest elderly populations in India, with an estimated 13-15 million individuals aged 60 and above. Aim & Objectives: To assess the physical health status & health seeking behaviour among elderly population. Material & Methods: The study was a community-based, cross-sectional research focused on the elderly population (60+ years) in Banda district, Uttar Pradesh, spanning 18 months. The final study included 400 participants, with 200 from rural and 200 from urban areas. A multi-stage random sampling technique was utilized. Semi-structured questionnaire was used for data collection after taking the informed consent. Results: Nearly 40% of elderly perceived their health as ‘Negative’. Eye, ENT, and musculoskeletal issues were more prevalent among urban population. In rural population had higher prevalence of gastrointestinal and central nervous system disorders, particularly in females. Majority of elderly contacted government facilities during illness (31.75%), which was slightly more in urban elderly, preferably among males. Elderly who did not utilized facilities during illness was 29.50%, which was highest among rural males (36.44%). Conclusion: Health perceptions were largely negative. Oral health issues were most common, followed by ENT disorders and eye problems. The main reasons for non-utilization of health services was affordability, particularly notable among urban females.